Cavitation tunnel analysis of radiated sound from the resonance of a propeller tip vortex cavity. (July 2016) - Pennings, Pepijn; Westerweel, Jerry; Terwisga, Tom van
Highlights: Open water inflow in a propeller contains insufficient excitation for a steady tip vortex cavity to produce significant sound. Broadband pressure fluctuations of propeller cavitation in wake inflow are shown to be generated by resonance of the tip vortex cavity. The model for a cavity resonance frequency (dispersion relation of n = 0 − mode at zero group velocity using Proctor vortex model) is capable of describing the measured dominant sound frequencies based on a limited number of propeller related parameters. Graphical abstract: Abstract: The goal of this study is to test the hypothesis that the resonance of a tip vortex cavity is responsible for high-amplitude broadband pressure-fluctuations, typically between 40 and 70 Hz, for a full scale propeller. This is achieved with a model propeller in a cavitation tunnel. Simultaneous high-speed video shadowgraphy and sound measurements show that a steady tip-vortex cavity behind a propeller in a uniform inflow does not produce significant sound in the relevant range of 0.5–1.2 kHz . The addition of an upstream wake does result in high amplitude sound. It appears that the dominant sound frequency is directly related to the resonance of the tip vortex cavity. A model for the tip-vortex cavity-resonance frequency, using a Proctor vortex model, is able to give an accurate description of the dominant sound frequencies.